MOLECULAR MORPHOLOGY OF SNAKE VENOM PROTEIN Trimeresurus insularis AFTER FREEZE DRYING DETECTED BY SCANNING ELECTRON MICROSCOPE - Adrianto, Steven; Sari, Tri Komala; Suarsana, I Nyoman; Suartini, I Gusti Ayu Agung (Universitas Syiah Kuala, 2025)
The high protein content in snake venom make venom samples prone damaged. Freeze drying is a solution to stabilize the protein in snake venom and the addition of excipients such as sugar and surfactant, can prevent negative impacts during freeze drying process. The purpose of this study was to examine the morphology of Trimeresurus insularis (T. insularis) snake venom protein molecules after freeze-drying with the addition of sucrose, Tween 80, and PBS (pH 7.2). In this study, venom from nine T. insularis snakes was used. Before freeze drying, the treated samples were supplemented with sucrose, Tween 80, and PBS (pH 7.2), while, the control sample was only supplemented with PBS (pH 7.2). After freeze drying, the morphology of both samples was observed using a scanning electron microscope at magnification of 100x and 3000x. The result showed that the control sample was damaged and resembled broken glass, whereas the treatment sample, although it also appeared as shattered glass, was more intact and exhibited finer and smaller flakes.